Solvent-driven chirality for luminescent self-assembled structures: experiments and theory. Issue 41 (19th October 2020) - Lochenie, Charles; Insuasty, Alberto; Battisti, Tommaso; Pesce, Luca; Gardin, Andrea; Perego, Claudio; Dentinger, Mike; Wang, Di; Pavan, Giovanni M.; Aliprandi, Alessandro; De Cola, Luisa
Abstract : Visualizing the interconversion from chiral helices to ribbons like-structures of self-assembled luminescent platinum complexes. Abstract : We describe, for a single platinum complex bearing a dipeptide moiety, a solvent-driven interconversion from twisted to straight micrometric assembled structures with different chirality. The photophysical and morphological properties of the aggregates have been investigated as well as the role of the media and concentration. A real-time visualization of the solvent-driven interconversion processes has been achieved by confocal microscopy. Finally, atomistic and coarse-grained simulations, providing results consistent with the experimental observations, allow to obtain a molecular-level insight into the interesting solvent-responsive behavior of this system.